2017
DOI: 10.1177/1741134317709509
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perceptions towards brand medicine and its effect on prescribing: A narrative review

Abstract: The purpose of this paper is to examine existing literature on physicians' perceptions towards brand medicines, to examine the extent to which brands influence drug prescription and whether pharmaceutical industry influences the prescription of brands, as well as to examine the loyalty of physicians to a brand when prescribing drugs or willingness to switch to generic drugs. Methods: Related articles published in different online databases from 2000 to 2017 were surveyed; 38 scientific articles indexed in Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
(183 reference statements)
4
14
0
Order By: Relevance
“…Since the opinions on ensuring safety measures and guaranteeing the quality of generic drugs compared to their original counterparts were also very positive, higher confidence in the processes of approval of medicinal products on the Czech market can be expected. Similarly, positive opinions have been reported in studies conducted in developed countries, where transparent, clear, and effective regulatory rules for generic substitution had been set up [27, 28]. On the other hand, healthcare professionals from countries with a less mature healthcare system appeared to have more concerned about the manufacturing sources of generics [20, 29, 30].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Since the opinions on ensuring safety measures and guaranteeing the quality of generic drugs compared to their original counterparts were also very positive, higher confidence in the processes of approval of medicinal products on the Czech market can be expected. Similarly, positive opinions have been reported in studies conducted in developed countries, where transparent, clear, and effective regulatory rules for generic substitution had been set up [27, 28]. On the other hand, healthcare professionals from countries with a less mature healthcare system appeared to have more concerned about the manufacturing sources of generics [20, 29, 30].…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, it is not possible to summarize the influence of age, length of practice or specialization on the physicians´ attitudes towards generic substitution. The results can be associated with the diversity of national healthcare policies, including various strategies of regulatory authorities, physicians´ knowledge, or the general development of the given country, as well as with the changes that may occur over time [11, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, Murshid and Mohaidin in 2017 examined existing literature on physicians' perceptions towards brand medicine, their loyalty to brands, and the influence of pharmaceutical companies, compared favorably with the work done by this researcher. 32 Murshid and Mohaidin in 2017 also noticed that physicians above 55 years old were over three times more hostile to generic medicine than younger physicians and prescribed branded medicine even when the generic counterpart was available.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations could be the poor trust of physicians in generic drugs as well as promotional incentives given to them by pharmaceutical companies. A review of physicians' perceptions on proprietary medicine concluded that the poor knowledge of physicians about biosimilar generic medicines was the main reason for such practice (17). A study in Jordan showed that 50-80% of physicians in Jordan were likely to oppose the replacement of brand drugs with generic substitutes (18).…”
Section: Discussionmentioning
confidence: 99%